2011
DOI: 10.3390/admsci1010003
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Group Conflict and Teamwork Quality: The Moderating Role of Leadership Styles

Abstract: Abstract:The study examines the extent to which task and relations oriented leadership moderate the impact of task and relationship conflict on teamwork quality. In a sample of 37 teams, the study shows that relationship oriented leadership is beneficial for dealing with relationship conflict, but it does not have the expected positive interaction effect with task conflict. The main practical implication of the results is that in order to mitigate the negative effects of intra-group conflict on teamwork qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Additionally, the results from the present study have demonstrated that task conflict did not have a strong, positive effect on relationship management. This was because task conflict on the one hand may promote informational diversity and on the other hand may cause tension among members (Curşeu 2011;De Dreu and Weingart 2003) that produces relational conflict (Gamero et al 2008) and negative influence on organizational practice(s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the results from the present study have demonstrated that task conflict did not have a strong, positive effect on relationship management. This was because task conflict on the one hand may promote informational diversity and on the other hand may cause tension among members (Curşeu 2011;De Dreu and Weingart 2003) that produces relational conflict (Gamero et al 2008) and negative influence on organizational practice(s).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, team members may have conflicting views on the adoption and implementation of quality management system. Task conflict refers to disagreements on the work to be done including the purposes of quality management, the allocation of resources, and the development and implementation of quality-related practices including the management of relationships with suppliers and other stakeholders (Curşeu 2011;Janssen et al 1999). Janis (1982) suggested that task-oriented disagreements prevent groupthink.…”
Section: Effect Of Task Conflict On Qmsmentioning
confidence: 99%
“…Leadership also used as a moderator in previous studies of (Zheng et al, 2019;Hussain & Younis, 2015) between envy and counterproductive work behavior (González-Navarro et al, 2018); between intragroup conflicts and teamwork, quality (Curşeu, 2011); between strategic human resource practices and job satisfaction (Hamid & Azhar, 2015); between management control and business excellence (Doeleman et al, 2012); between follower characteristics and follower work engagement (Zhu et al, 2009). Thus, we suggest the following hypothesis: H5: Leadership moderates the relationship between [a) job stress; b) work environment; c) overall compensation benefits and pay] and employees' job satisfaction.…”
Section: The Moderation Effectsmentioning
confidence: 99%
“…Because leaders guide, direct and often inspire their employees or teams, followers may instinctively look to their direction when conflicts occur. As such, many leaders employ conflict handling techniques to successfully manage conflict [9].…”
Section: Literature Reviewmentioning
confidence: 99%